Pendekatan Perencanaan Desain Wahana Game Esport di Surabaya dengan Menggunakan Konsep Futuristik - Ardiyanto, Rachman; Salisnanda, Randy Pratama; Laksono, Sigit Hadi (Institut Teknologi Adhi Tama Surabaya, 2021)
Abstract. Online games are games that require online-based playing devices and if they are competed in a sport, then the sport is called esports. Meanwhile, there is a device that has just emerged to be able to experience real life in the game called Virtual Reality / VR. With VR, it can change the image of a passive game to an active one. Currently, many games are commonly played, competing to make it real by using VR. So it requires a space that creates a special vehicle and place for VR game users. However, in Surabaya, there are no special places to accommodate game fans. In fact, it has the potential to create excellent facilities and make introverted gamers more productive and socially minded. The type of research method used is descriptive method, starting from the case study of LigaGameTV, Jakarta which produces facilities for current and future game fans, as well as knowing the problems that exist for game fans. Then the case study of Spazio Surabaya and Werk12, Germany. Resulting in the concept of